Etude De Quelques Proprietes Biologiques De Ocimum Gratissimum L., Une Lamiaceae Recoltee A Daloa (CÃ´te d’Ivoire) - Kouassi, ElisÃ©e Kporou; Ouattara, Sitapha; Seguin, Cendrine; Fournel, Sylvie; Frisch, Benoit (European Scientific Journal, ESJ, 2018)
Introduction: Ocimum gratissimum is used in traditional Ivorian medicine for its multiple therapeutic virtues. Scope: Evaluate the biological properties of the essential oil of this plant. Methods: Antitumor activity was assessed using the MTS colorimetric assay on six (06) cell lines, the antifungal activity was evaluated by double dilution slant method on four (04) strains of clinical fungi, the potential antioxidant was determined by the DPPH test. Results: The strongest cytotoxic activity was obtained on Jurkat (T lymphoma) with an IC50 = 80 Î¼g / ml. The best antifungal activity was observed on C. albicans with MIC and FMC values obtained at 12.5 Î¼g / ml. Antioxidant activity was evaluated at F = 187 Â± 1.57 mM Trolox / ml or (I = 38 Â± 0.74%). Conclusion: The essential oil has interesting biological properties like as cytotoxic, antifungal and antioxidant